2008
DOI: 10.1016/j.fsc.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Body Dysmorphic Disorder

Abstract: Body dysmorphic disorder occurs in 1% of the general population, rising to 6 to 16 times higher in patients presenting to plastic surgery clinics. This article discusses ways to identify patients who have body dysmorphic disorder and options for treating these patients, whether or not to perform cosmetic surgery, and when to refer for psychologic or psychiatric counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
0
17
0
4
Order By: Relevance
“…[8][9][10][12][13][14][15][16][17][18][19][20][21][22] These studies were excluded from this review because body dysmorphic disorder is already acknowledged as a psychopathologic condition with an adverse effect on a patient's satisfaction after cosmetic surgery. [8][9][10][12][13][14][15][16][17][18][19][20][21][22] These studies were excluded from this review because body dysmorphic disorder is already acknowledged as a psychopathologic condition with an adverse effect on a patient's satisfaction after cosmetic surgery.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][12][13][14][15][16][17][18][19][20][21][22] These studies were excluded from this review because body dysmorphic disorder is already acknowledged as a psychopathologic condition with an adverse effect on a patient's satisfaction after cosmetic surgery. [8][9][10][12][13][14][15][16][17][18][19][20][21][22] These studies were excluded from this review because body dysmorphic disorder is already acknowledged as a psychopathologic condition with an adverse effect on a patient's satisfaction after cosmetic surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Certains de ces cas peuvent avoir des suites médico-légales, plaintes ou agressions contre le chirurgien, suicide du patient [117]. Ces dernières années, il semble y avoir une prise de conscience croissante du risque associé aux traitements esthétiques médi-caux dans le BDD si l'on en juge par la répétition des revues de la question dans les journaux des spécialités les plus concernées, principalement de chirurgie esthétique et dermatologique [43,85,[118][119][120][121]. L'avis général, fondé sur des études rétros-pectives, exprimé dans ces revues, est que le BDD n'est pas amélioré par les traitements du défaut et que la chirurgie, en particulier, n'est pas indiquée chez les patients BDD.…”
Section: Traitements Non Psychiatriques Et Dépistage Du Bddunclassified
“…Of interest, the rate of body dysmorphic disorder in cosmetic patients has been reported to be 5 to 15 percent. 1 Moreover, Ende et al 2 reported that 84 percent of surgeons in their study failed to recognize body dysmorphic disorder before operating on the patient. Thus, the fact that Dr. Constantian discovered postoperatively that 2 percent of patients exhibited signs of body dysmorphic disorder is a testimony to his ability to weed out that problem before surgery.…”
mentioning
confidence: 99%